An evaluation of the process capability implications of the requirements of ISO/IEC 20000‐1. Issue 12 (5th June 2014) - Walker, Alastair; Coletta, Antonio; Sivaraman, Rama
ABSTRACT This technical contribution explores the process capability implications of the requirements of ISO/IEC 20000‐1. The foundation of the methodology that is used to determine the linkages between each requirement and the notional process capability attribute that is supported is considered. The results of analyses are then presented of the implied clause process capability profile from the perspective of all the clauses, on one hand, and from individual clauses, on the other hand. The implications of these process capability insights to the design of an organizational maturity model applicable to ISO/IEC 20000‐1 are then considered. Copyright © 2014 John Wiley & Sons, Ltd.